Strategic Decision Making for Facility Optimisation in Indonesia’s Gunung Kemala Oil Field Using AHP - Agung Wibowo; Pri Hermawan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2026)
The focus of this research is the strategic optimisation of surface production facilities under capital and governance constraints, in Indonesia’s brownfield oil assets of Gunung Kemala (GNK), within a state-owned-enterprise (SOE) governance context. An integrated Multi Criteria Decision Making (MCDM) model is formulated, jointly involving Value-Focused Thinking (VFT) to organise policy objectives, Kepner–Tregoe (KT) Decision Analysis to filter “Must” criteria and “Want” criteria, and the Analytical Hierarchy Process (AHP) for ranking four strategic alternatives: i.e., constructing a new facility, upgrading current facilities, utlisation of idle assets and renting third-party infrastructures. The raw data was obtained through conversation, focused group discussion and expert pairwise comparison with seven experts from domain knowledge. The comparison results reveal that utilization of idle assets appears as the biggest preferred alternative (global priority weight = 0.547) and compared to greenfield & brownfield expansions. This dominance derives from the capital efficiency, faster deployment time, reduced regulatory exposure and better alignment with asset-governance constraints. This research presents an integrated VFT–KT–AHP decision framework that is designed specifically for the brownfield bottle necks in emerging-market upstream settings. It expands the traditional AHP application from technical based ranking to incorporate issues in governance feasibility and asset utilization strategies as an internal capital allocation decision logic, providing a solution model that is applicable with other SOE oriented energy systems.